2009
DOI: 10.1002/job.610
|View full text |Cite
|
Sign up to set email alerts
|

Emotional competence and work performance: The mediating effect of proactivity and the moderating effect of job autonomy

Abstract: SummaryThis paper proposes and tests a model where emotional competence influences work performance through employees' proactive behaviors toward their supervisors. Results from 196 supervisor-employee pairs supported that emotional competence was positively associated with proactive behaviors, and proactive behaviors were positively associated with both task effectiveness and social integration. In addition, proactive behaviors significantly mediated the relationships between emotional competence and work per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 49 publications
3
73
0
6
Order By: Relevance
“…Increasing OCB requires more psychological empowerment (Hwang, 2005;Maurer et al, 2002;Peccei and Rosenthal, 2001;Spector and Fox, 2002;Tsaur et al, 2004;Wat and Shaffer, 2005;Yen et al, 2004). Kim et al (2009) conducted research on managers and employees in hotels in South Korea, concluding that employee proactive behavior mediated emotional competence on job performance. Chen (2008) investigated POS and job performance and revealed that high levels of employees' POS produced positive OCB; moreover, OCB improved staff performance itself.…”
Section: The Mediating Effects Of Ocbmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing OCB requires more psychological empowerment (Hwang, 2005;Maurer et al, 2002;Peccei and Rosenthal, 2001;Spector and Fox, 2002;Tsaur et al, 2004;Wat and Shaffer, 2005;Yen et al, 2004). Kim et al (2009) conducted research on managers and employees in hotels in South Korea, concluding that employee proactive behavior mediated emotional competence on job performance. Chen (2008) investigated POS and job performance and revealed that high levels of employees' POS produced positive OCB; moreover, OCB improved staff performance itself.…”
Section: The Mediating Effects Of Ocbmentioning
confidence: 99%
“…In summary, OCB may mediate among these variables. After studying managers and employees from hotels in South Korea, Kim et al (2009) noted that proactive behavior can affect job performance; proactive behavior is one medium between emotional competence and job performance.…”
Section: Introductionmentioning
confidence: 98%
“…The first psychological factor is the emotional stability of feedback participants. In the case of feedback-seeking behavior, emotional stability is related to a better ability to face and accept negative feedback (Moeller, Robinson, 2010) and higher willingness to seek feedback from supervisors (Kim et al 2009). Emotional stability also has a beneficial impact on the constructiveness of the feedback-giving process (Raver et al, 2012).…”
Section: Psychological Factors Of the Feedback-related Behaviormentioning
confidence: 99%
“…Despite having its advantages, the application of negative feedback also faces several issues such as defensiveness of feedback-receivers and destructive criticism in case of feedback-giving behavior (Leung, Su & Morris, 2001;Raver et al, 2012;Steelman & Rutkowski, 2004) and avoidance of negative information and neglecting direct methods in case of feedback-seeking behavior (Ashford et al, 2016). Although these issues are the result of more complex factors, they are significantly influenced by psychological factors such as emotional stability (Kim et al, 2009), attachment style (Brennan et al, 1998), low level of self-esteem (Baumeister et al, 2003), and goal orientation (VandeWalle, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Proactivity has been connected to success on both individual and organizational levels (Seibert et al, 1999;Baer and Frese, 2003;Frese et al, 2007;Kim et al, 2009), and it correlates with idea creativity and initial engagement in the creative process (Binnewies et al, 2007) as well as the amount of rewarded improvement suggestions (Frese et al, 1999). Furthermore, Baer and Frese (2003) have found process innovations to increase performance only in a climate of initiative, or proactivity.…”
Section: Idea Advancement As Proactive Behaviourmentioning
confidence: 99%